2021
DOI: 10.3389/fmolb.2021.659058
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Multi-Omics Characterization of Escherichia coli K-12 Adapted to Chlorhexidine Identifies the Role of MlaA and Other Cell Envelope Alterations Regulated by Stress Inducible Pathways in CHX Resistance

Abstract: Chlorhexidine (CHX) is an essential medicine used as a topical antiseptic in skin and oral healthcare treatments. The widespread use of CHX has increased concerns regarding the development of antiseptic resistance in Enterobacteria and its potential impact on cross-resistance to other antimicrobials. Similar to other cationic antiseptics, resistance to CHX is believed to be driven by three membrane-based mechanisms: lipid synthesis/transport, altered porin expression, and increased efflux pump activity; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…To verify CHX resistance phenotypes of the various E. coli strains prior to RFDMIA analysis, AST was performed with E. coli gene deletion mutants, plasmid transformants, and CHX-adapted isolates to determine their CHX MIC values (Table 1 ). As previously reported 22 , AST of CHX-adapted E. coli CHXR1 demonstrated a fourfold increase in CHX MIC values when compared to the unadapted E. coli BW25113 strain (Table 1 ). Prior genetic analyses of CHXR1 in a recent study revealed that this adapted isolate possesses numerous gene mutations, including deleterious mutations to mlaA and its upstream promoter 22 .…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…To verify CHX resistance phenotypes of the various E. coli strains prior to RFDMIA analysis, AST was performed with E. coli gene deletion mutants, plasmid transformants, and CHX-adapted isolates to determine their CHX MIC values (Table 1 ). As previously reported 22 , AST of CHX-adapted E. coli CHXR1 demonstrated a fourfold increase in CHX MIC values when compared to the unadapted E. coli BW25113 strain (Table 1 ). Prior genetic analyses of CHXR1 in a recent study revealed that this adapted isolate possesses numerous gene mutations, including deleterious mutations to mlaA and its upstream promoter 22 .…”
Section: Resultssupporting
confidence: 83%
“…As previously reported 22 , AST of CHX-adapted E. coli CHXR1 demonstrated a fourfold increase in CHX MIC values when compared to the unadapted E. coli BW25113 strain (Table 1 ). Prior genetic analyses of CHXR1 in a recent study revealed that this adapted isolate possesses numerous gene mutations, including deleterious mutations to mlaA and its upstream promoter 22 . As shown in Table 1 , only plasmid complementation with a wildtype copy of mlaA reverted this isolate back to CHX susceptible phenotypes observed for the unadapted WT 22 .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations